The Challenges and Future of Advanced Therapies - Rehan Haider; Asghar Mehdi; Geetha Kumari; Zameer Ahmed; Sambreen Zameer (Contemporary Journal of Applied Sciences, 2024)
Advanced therapies, including gene therapies, cell-based therapies, and tissue engineering, have emerged as revolutionary approaches in medicine. These therapies hold immense promise for treating previously untreatable diseases by targeting underlying causes at the molecular and cellular levels. However, their translation from laboratory breakthroughs to clinical applications is accompanied by significant challenges that must be addressed to realize their full potential. One major challenge lies in the complexity and variability of patient responses. The personalized nature of advanced therapies demands precise customization of each individual, necessitating the development of robust biomarkers and predictive models. Ensuring the safety of these therapies is paramount. Unforeseen immune reactions, off-target effects, and long-term consequences require stringent preclinical testing and vigilant post-market surveillance. Manufacturing scalability is another hurdle. Unlike traditional pharmaceuticals, advanced therapies often involve intricate processes specific to each patient. Standardizing and automating these processes, while maintaining product quality and consistency, are critical obstacles. Moreover, the high costs associated with research, development, manufacturing, and delivery hinder accessibility and affordability, raising concerns about equitable patient access. The regulatory landscape also requires adaptation to accommodate the unique attributes of advanced therapies. Striking a balance between timely access to patients and comprehensive evaluation of safety and efficacy challenges regulatory agencies globally